INNOVATIVE DEVELOPMENT OF NON-FORMAL EDUCATION IN UKRAINE: DEFINITION OF SOFT SKILLS - Boiko, Anna (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article is devoted to the urgent issue of the formation of students’ soft skills in the process of innovative development of non-formal education that enables them to become successful in the future. The aim of the article is to define the term “soft skills” in the context of innovative development of non-formal education in Ukraine based on the analysis of current national and international studies and normative documents. To implement the research objectives, the following theoretical methods were used such as content-analysis and generalization of scientific research in order to determine the main approaches of defining the key notions of students’ soft skills in institutions of out-of-school education, systematization and comparison of theoretical data in order to identify the main components of students’ soft skills in non-formal education. According to the results of the research, the notion of “soft skills” is defined as a set of intangible personal qualities, traits, attributes, habits and attitudes that can be used in many different types of jobs. The students’ soft skills include creativity and innovation, critical thinking, problem-solving, decision making, learning to learn, metacognition, communication, collaboration, citizenship (local and global), life and career skills, personal and social responsibility (including cultural awareness and competence), etc. It is found that non-formal education should emphasize developing students’ soft skills, such as critical thinking, teamwork, problem-solving, creativity, conflict resolution, and communication skills, which can be used across a range of occupational fields. It is concluded that innovations in non-formal education need to focus efforts on access, inclusion, and sustainability in the provision, such as: ensuring soft skills learning, developing educational programs for students in providing relevant soft skills, training well-qualified educators for developing students' soft skills in institutions of out-of-school education. The practical significance of the research is that its materials can be used to develop educational programs for out-of-school education, in the system of professional teacher training and pedagogical practice of students., The results obtained provide a basis for future research that should be dedicated to the development of educational programs for the formation of students’ soft skills in institutions of out-of-school education.